Perception of creative identities by artistic and non-artistic individuals: consequences for management - Szostak, Michał (Creativity Studies, 2023)
The interdisciplinary research on the perception of creative identities like artists, creators,entrepreneurs, leaders, and managers brings substantial conclusions for understanding the way of thinking, internal features, and motivations of decisions of individuals with and without artistic factor. For this purpose, an international quantitative examination of 160 individuals was undertaken. The research exhibited that individuals with and without artistic identity perceive artists, creators, entrepreneurs, leaders, and managers statistically similar (chi-square test of independence used, p < 0.001). The negative verification of the hypotheses was astonishing and a novelty in the investigated area. The novelty should be seen as an artistic potential existing in each individual. The additional qualitative analysis of the 50 features constituting the investigated identities revealed that individuals with and without artistic identity see particular features of these identities slightly differently (the most important, the least important, and the most equally perceived features were described in detail). The outcomes were discussed with the literature on the subject, confirming most other researchers’ theses and revealing some contradictions and can be used to understand the qualities of artistic identity and the perception of investigated identities by individuals, groups, and societies dominated by persons with and without artistic factors. The applicability of the results is broad, mainly due to the role of artistry in today’s world as potential laying in every individual. Specific triggers should be catalyzed instead of looking for artist-born individuals. The education process of artists should focus on revealing artistic potential underlining the role of inspiration, and discovering the motifs of artistic activity.